Hostile Parent Firms and Child Firm Performance - Sascha Walter; Simon Heinrichs; Achim Walter (ZBW - Leibniz-Informationszentrum Wirtschaft, 2013)
We investigated how and when parent hostility (degree to which a parent firm disapproves the spawning of an own spin-out) affects spin-out performance and how spin-outs can effectively react to it. Analyses of 144 technology spin-outs support our arguments that spin-outs suffer from hostility. Hostility consequences are, however, less severe if market turbulence is high or if the spin-out pursues effective network development.
Keywords: M13; 650; parent-child relationship